Advanced Modulation Formats For High-Speed Photonic Access Networks - Lee, Lian Hong (2009)
This thesis aims to research on an advanced optical modulation format for high-speed photonic access networks by studying the optical signal modulated through intensity, phase, and polarization modulation format in an optical communication system link. The analysis on the hybrid combination of the three modulation formats was also carried out.